Conflict or Coherence in the EU Green Transition? - A Critical Analysis of the Interplay between the Critical Raw Materials Act and the Corporate Sustainability Due Diligence Directive in relation to Sami Indigenous Rights - Ehrenborg,Hanna (2024)
In 2023, the Swedish state-owned enterprise LKAB garnered global attention by announcing the discovery of Europe’s largest rare earth elements deposit in Kiruna, Sweden’s northernmost town. This discovery is highly symbolic for the European Union (EU), given the critical role rare earth metals play in advancing clean energy technologies. However, as the deposit is situated on Indigenous land, it has also reignited debates about the impact of extractive activities on Indigenous territories. Against the backdrop of a rapidly surging demand for critical raw materials (CRMs) driven by the green transition, this thesis examines the growing tension between the EU’s pursuit of CRMs, its sustainability commitments, and the protection of Indigenous Peoples’ rights, using the LKAB deposit as a case study. Globally, there has been a growing recognition of Indigenous Peoples’ rights, particularly in relation to extractive activities on their traditional lands. Yet, resource extraction often occurs in breach of these rights, even in welfare states like Sweden, presenting a paradox that this thesis seeks to explore. By focusing on the Sami – the EU’s only recognized Indigenous People – this study sheds light on the relatively under-researched relationship between the Sami, mining in Sápmi, and EU law. The thesis employs a combination of a legal doctrinal method, critical evaluation, and a law-in-context approach to analyze Swedish, EU, and international legal frameworks in this context. The study examines the interplay between two key EU legal instruments both introduced under the wide-ranging European Green Deal: the Critical Raw Materials Act (CRMA) and the Corporate Sustainability Due Diligence Directive (CSDDD). The CRMA seeks to enhance the EU’s self-sufficiency by increasing the supply of CRMs within Europe through streamlined permit-granting processes, while the CSDDD aims to ensure sustainable and responsible corporate practices. However, these frameworks encompass conflicting policy objectives and raise concerns about their alignment with international standards on Indigenous Peoples’ human rights. The findings underscore the persistent marginalization of the Sami within the EU’s regulatory framework, as well as significant shortcomings in Swedish mining laws that fail to align with international standards. The CRMA and the CSDDD lack coherence and offer inadequate safeguards for Indigenous Peoples’ rights. This creates a fragmented policy landscape where companies like LKAB can adhere to minimal national standards while disregarding Sami rights recognized under international law. The thesis emphasizes the urgent need for stronger policy alignment to protect Indigenous rights in the EU’s green transition and calls for greater recognition of Sami rights in EU policy-making. It also advocates for a fundamental reform of Swedish legislation to bridge the gap between national and international legal standards, aiming to finally address the Sami’s protracted legal limbo.
Keywords: public international law; EU law; business and human rights; Indigenous Peoples' rights; self-determination; Sami; policy coherence; critical raw materials; due diligence; green transition; LKAB; extractive industries